Constraints in nurses´ use of HIV protective barriers in the care of PLWHA in the University College Hospital (UCH), Ibadan, Nigeria (2009)
This survey examines the constraints limiting nurses’ use of protective barriers in the care of people living with HIV/AIDS in Ibadan, Nigeria. 270 females and 5 male nurses working in UCH were purposively selected. A self-developed questionnaire was used during data collection. Data was analyzed using descriptive statistics and chi square. Results about nurses’ use of protective devices (eg gloves) showed that 206 (94.2%) use PB always, 15 (5.5%) frequently use PB and 1(0.4%) occasionally use PB. Chi-square test shows significant differences between constraints in the use of PB in the care of PLWHA and adherence to HIV/AIDS universal precautions (X1=15.22, 1df, p<0.05). It was concluded that nurses in the selected setting were faced with constraints in the use of PB and as such were inadequately protected from blood-borne diseases especially when caring for PLWHA